Health Literacy and Quality of Life in Young Adults From The Belgian Crohn's Disease Registry Compared to Type 1 Diabetes Mellitus - Carels, Constance; Wauters, Lucas; Outtier, An; Baert, Filip; Bossuyt, Peter; Colard, Arnaud; De Looze, Danny; Ferrante, Marc; Goegebuer, Alexander; Hauser, Bruno; Hilbrands, Robert; Hoffman, Ilse; et al. (Frontiers in Pediatrics, 2021)
Background and Aims: The management of chronic inflammatory bowel diseases in youth is challenging. We aimed to determine health literacy (HL), quality of life (QoL), social integration and clinical outcomes in young adults from the BELgian CROhn’s disease registry (BELCRO) in comparison to type 1 diabetes mellitus (DM) as a control. Methods: In this prospective and observational study, young adults with Crohn’s disease (CD) diagnosed < 18 yrs and with > 5 yrs disease duration and a comparable group of patients with DM completed validated HL, QoL and work productivity and activity impairment questionnaires (HLS-EU-Q16, EQ-5D-5L and WPAI). HL was scored as sufficient (13-16), problematic (9-12) or inadequate (0-8). QoL was dichotomized into ‘no problems’ (EQ-5D level 1) or ‘problems’ (EQ-5D levels 2 to 5). Non-parametric (Mann-Whitney U) analyses and Spearman correlations were performed. Results: A total of 52 CD (median [IQR] age of 25.0 [23.8-27.0], 64% male) and 50 DM (age 20.0 [19.0-22.0], 50% male) patients were included. HL was 14.0 [11.0-16.0] for CD and 14.0 [11.3-14.8] for DM (p= 0.6) with similar proportions of sufficient (60 vs. 68%, p= 0.4), problematic (34 vs. 26%, p= 0.3) and inadequate HL (both 6%, p= 1). Although QoL was comparable for CD and DM (77.0 [68.8-82.0] vs. 75.0 [65.0-80.0] %, p=0 .4), CD had a trend for higher pain/discomfort (50 vs. 32%, p= 0.06). HL and QoL correlated in CD (r= 0.6, p< .001) and DM patients (r= 0.6, p< 0.001). Fewer CD patients with recent hospitalization/surgery had sufficient HL (31 vs. 69%, p= 0.01) and had lower QoL (70.0 [60.0-77.0] vs. 80.0 [70.0-85.0], p= 0.04) compared to those without. Conclusions: Selected young Belgian adults suffering from CD for >5 years have similar and sufficient HL compared to DM patients. However, CD patients requiring hospitalization/surgery have lower HL, which indicates the need for targeted educational programs.